Bio-inspired materials and sensing systems - Biggins, Peter; Biggins, Peter; Hiltz, John; Kusterbeck, Anne (NBN International, 2011)
This unique book provides an overview of bio-inspired sensors and systems together with examples of how they are being implemented. Readers gain an awareness of the complexity and versatility of bio-inspired components and an understanding of how these technologies can be applied in a variety of operational scenarios.